Conductive and antistatic rubber composition and vulcanized rubber as well as preparation method and application of conductive and antistatic rubber composition and vulcanized rubber

By using carbon-based filler and styrene butadiene rubber latex composite and in-situ reduction technology in conductive rubber materials, combined with vulcanization treatment, the problems of poor dispersion and high cost of conductive filler are solved, and the conductive performance is improved and cost reduction is reduced. It is suitable for use in Flexible sensors and antistatic materials for wearable devices.

CN119144066AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310716226.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

The conductive fillers in existing conductive rubber materials are not easily dispersed efficiently, which affects the improvement of conductive performance and is relatively high in cost, which limits the development of wearable devices.

Method used

Carbon-based fillers such as graphene and graphene oxide are combined with styrene butadiene rubber emulsion, and are efficiently dispersed by emulsion composite method, and are reduced in situ to highly conductive fillers during the recombination process. Combined with vulcanization treatment, conductive and antistatic rubber compositions are prepared. , reduce volume resistivity.

Benefits of technology

The conductive performance is improved, and the volume resistivity range is suitable for the flexible piezoresistive sensor requirements of wearable devices, while reducing material costs, and is suitable for use as an antistatic rubber material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144066A_ABST
    Figure CN119144066A_ABST
Patent Text Reader

Abstract

The invention relates to the field of rubber, and discloses a conductive and antistatic rubber composition and vulcanized rubber as well as a preparation method and application thereof. The rubber composition comprises base rubber, a carbon-based filler, a vulcanizing agent, a vulcanization accelerator, a vulcanization activator and an anti-aging agent, wherein the base rubber is butadiene styrene rubber; the carbon-based filler is graphene and / or graphene oxide; relative to 100 parts by weight of the base rubber, the content of the carbon-based filler is 0.8-6.5 parts by weight. The vulcanized rubber can meet the use requirements of conductive rubber materials (102 omega.m to 106 omega.m) of flexible piezoresistive sensors of wearable equipment, the volume resistivity is adjusted to be 106 omega.m to 109 omega.m, and the vulcanized rubber can also be used as an antistatic rubber material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber, and in particular to a conductive and antistatic rubber composition and vulcanized rubber, and a preparation method and application thereof. Background Art

[0002] The volume resistivity of conductive rubber materials ranges from 10 2 ~10 6 Ω·m, conductive rubber materials are widely used in various types of pressure sensors. Piezoresistive sensors have attracted widespread attention due to their simple device structure, low energy consumption, large sensitivity coefficient, and good frequency response. Among them, conductive rubber sensors often replace metal material piezoresistive sensors and inorganic conductive material piezoresistive sensors because of their conductive function, low density, corrosion resistance, and conductivity that can be adjusted within dozens of orders of magnitude. They are widely used in production and life. The volume resistivity range of antistatic rubber materials is 10 6 ~10 9 Ω·m, it is widely used in antistatic shells, antistatic conveyor belts, antistatic soles, IC storage boxes, copy and textile rollers, as well as antistatic rubber sheets and strips.

[0003] CN105670297A discloses a conductive rubber material for a flexible sensor, a preparation method and an application thereof, wherein the conductive rubber material for a flexible sensor comprises the following components in the following weight proportions: 100 parts of a silicone rubber matrix, 5-100 parts of a conductive filler, 5-30 parts of a modified white carbon black, and 0.1-10 parts of a coupling agent, and the conductive rubber material is prepared by dispersing the conductive filler in a rubber material and cross-linking it by electron beam or gamma ray radiation. The silicone rubber matrix comprises a molecular main chain structure composed of alternating silicon atoms and oxygen atoms, and further, the silicone rubber matrix is ​​at least one of dimethyl silicone rubber, methyl vinyl silicone rubber, methyl vinyl phenyl silicone rubber, phenylene silicone rubber, fluorosilicone rubber, nitrile silicone rubber, and borosilicate rubber. The conductive filler is at least one of conductive carbon black, nanographite, carbon nanotubes, silver-plated powder, nickel powder, and nickel-plated powder. The resistivity of the conductive rubber material is in the range of 2.0×10 3 Ω·m to 1.0×10 10 Ω·m. In this patent, the conductive rubber matrix uses expensive silicone rubber, the conductive filler uses conductive carbon black, metal powder, etc., and the processing method uses a melt compound method. The conductive filler is not easy to disperse efficiently in the rubber matrix, which affects the further improvement of the conductive performance.

[0004] With the popularity of smart products, wearable electronic devices present a huge market prospect, but achieving high sensitivity, high resolution, low-cost manufacturing and complex signal detection of flexible electronic sensors is still a big challenge. As one of the main core component materials of sensors, the breadth of the adjustable resistivity range and manufacturing cost of conductive rubber materials will affect the future development of wearable devices.

[0005] Therefore, it is necessary to propose a method for preparing a conductive rubber composition that can solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem in the prior art that conductive fillers are not easy to be efficiently dispersed in a rubber matrix, which affects the further improvement of conductive performance, and to provide a conductive, antistatic rubber composition and vulcanized rubber and a preparation method and application thereof. The vulcanized rubber has a wide volume resistivity and is low in cost.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a conductive and antistatic rubber composition, wherein the rubber composition comprises a base rubber, a carbon-based filler, a vulcanizer, a vulcanization accelerator, a vulcanization activator and an antioxidant, the base rubber is styrene-butadiene rubber; the carbon-based filler is graphene and / or graphene oxide; and the content of the carbon-based filler is 0.8-6.5 parts by weight relative to 100 parts by weight of the base rubber.

[0008] The second aspect of the present invention provides a vulcanized rubber, wherein the vulcanized rubber is obtained by mixing and vulcanizing the conductive and antistatic rubber composition described above.

[0009] The third aspect of the present invention provides a method for preparing the aforementioned vulcanized rubber, wherein the method comprises:

[0010] (1) dispersing the carbon-based material into water to form a suspension containing the carbon-based material;

[0011] (2) using a saturated NaCl aqueous solution as a flocculant, mixing the base rubber with the suspension for co-coagulation, and filtering, washing and drying the obtained co-coagulated solid to obtain a base rubber / carbon-based material masterbatch;

[0012] (3) Mixing and vulcanizing the base rubber / carbon-based material masterbatch, the vulcanizing agent, the vulcanization accelerator, the vulcanization activator and the antioxidant to obtain a vulcanized rubber.

[0013] A fourth aspect of the present invention provides a use of the aforementioned vulcanized rubber in the preparation of a flexible resistance sensor.

[0014] A fifth aspect of the present invention provides a use of the aforementioned vulcanized rubber in the preparation of an antistatic rubber material.

[0015] Through the above technical scheme, the present invention efficiently disperses the carbon-based material in the base rubber by emulsion compounding method, and in situ reduces it to a highly conductive filler during the compounding process, so that the vulcanized rubber composition has excellent conductive properties, and its volume resistivity ranges from 10 2 Ω·m to 10 9 Ω·m, which can meet the needs of conductive rubber materials for flexible piezoresistive sensors of wearable devices (10 2 Ω·m to 10 6 Ω·m) usage requirements, adjust the volume resistivity to 10 6 Ω·m to 10 9 Ω·m, and can also be used as an antistatic rubber material. At the same time, the rubber composition matrix of the present invention adopts a relatively cheap styrene-butadiene rubber instead of the commonly used expensive rubber matrix such as silicone rubber. Due to the efficient dispersion technology of the conductive filler, a small amount of conductive filler can have a lower volume resistivity, so it has a lower material cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the relationship curve between the volume resistivity and the graphene oxide content of the vulcanized rubber prepared in Examples 1-4 and the vulcanized rubber prepared in Comparative Examples 1-3. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] As mentioned above, the first aspect of the present invention provides a conductive and antistatic rubber composition, wherein the rubber composition includes a base rubber, a carbon-based filler, a vulcanizer, a vulcanization accelerator, a vulcanization activator and an antioxidant, the base rubber is styrene-butadiene rubber; the carbon-based filler is graphene and / or graphene oxide; and the content of the carbon-based filler is 0.8-6.5 parts by weight relative to 100 parts by weight of the base rubber.

[0019] The inventors of the present invention have discovered that efficient dispersion of conductive fillers is an important factor in significantly reducing the volume resistivity of rubber materials. If the dispersion effect of conductive fillers is not ideal, a large amount of expensive conductive fillers need to be filled in order to prepare rubber materials with low resistivity, which will undoubtedly increase material costs and affect the mechanical properties of rubber composites.

[0020] The inventors of the present invention have found in the process of in-depth research that if a carbon-based filler (graphene and / or graphene oxide) is compounded with a styrene-butadiene rubber latex, for example, due to the polarity of graphene oxide, it can interact with the surfactant on the surface of the styrene-butadiene rubber latex particles, effectively improving the dispersion effect of graphene oxide and styrene-butadiene rubber, and reducing the volume resistivity of the rubber composite material at a lower graphene oxide dosage; in addition, graphene oxide contains more sp 3 Carbon atoms have weak conductivity. If a reducing agent is used to in-situ reduce graphite oxide to graphene during the efficient dispersion of graphite oxide, sp 3 A large number of carbon atoms are converted into sp 2 Carbon atoms, after reduction, have more freely moving electrons in graphene, which can significantly reduce the volume resistivity of rubber composites.

[0021] According to the present invention, preferably, the content of the carbon-based filler is 1-6.2 parts by weight, more preferably 1-5 parts by weight, relative to 100 parts by weight of the base rubber. In the present invention, if the content of the carbon-based filler is too low, the resistivity of the composition is very low and cannot meet the requirements for making a flexible resistance sensor; if the content of the carbon-based material is too high, the elasticity of the composition decreases, the elongation at break is too low, and it is not suitable as a material for a flexible resistance sensor.

[0022] According to the present invention, the base rubber is in the form of a base rubber emulsion; wherein the solid content of the base rubber emulsion is 10-30wt%, preferably 15-30wt%. In addition, in the present invention, it should be noted that the base rubber emulsion refers to an emulsion with an organic solution of the base rubber as a dispersed phase and water as a continuous phase; wherein the organic solution can be one or more of gasoline, cyclohexane, heptane, carbon tetrachloride, chloroform, ethylene dichloride and chlorobenzene.

[0023] According to the present invention, relative to 100 parts by weight of styrene-butadiene rubber, the content of the vulcanizing agent is 1-3 parts by weight, the content of the vulcanization activator is 3-6 parts by weight, the content of the vulcanization accelerator is 0.5-2 parts by weight, and the content of the antioxidant is 0.5-2 parts by weight; preferably, relative to 100 parts by weight of styrene-butadiene rubber, the content of the vulcanizing agent is 1.25-2 parts by weight, the content of the vulcanization activator is 3.5-6 parts by weight, the content of the vulcanization accelerator is 1-2 parts by weight, and the content of the antioxidant is 1-2 parts by weight.

[0024] According to the present invention, preferably, the carbon-based material is graphene oxide. The number of graphene oxide layers dispersed in the rubber composition is 1-16 layers, preferably 9-16 layers. In addition, the number of graphene layers is preferably 9-16 layers.

[0025] In the present invention, the basic structure of graphene and graphene oxide is a layered carbon atom layer, which is easy to form a conductive network. The conductivity of graphene oxide is further improved after reduction, and the resistivity of the rubber composition is further reduced.

[0026] According to the present invention, the vulcanizing agent is a sulfur donor. Preferably, the vulcanizing agent is selected from one or more of ordinary sulfur S, oil-extended insoluble sulfur IS and sulfur-based vulcanizing agents.

[0027] According to the present invention, the vulcanization activator is an inorganic activator and / or an organic activator; wherein the inorganic activator includes one or more of indirect zinc oxide, direct zinc oxide and activated zinc oxide; the organic activator includes one or more of stearic acid, lauric acid and caprylic acid; preferably, the vulcanization activator is stearic acid.

[0028] According to the present invention, the vulcanization accelerator is selected from one or more of sulfenamide accelerators, thiazole accelerators, thiuram accelerators and guanidine accelerators; preferably, the vulcanization accelerator is accelerator CZ.

[0029] According to the present invention, the antioxidant is selected from one or more of amine antioxidants, quinoline antioxidants and benzimidazole antioxidants; preferably, the antioxidant is antioxidant 4010.

[0030] The second aspect of the present invention provides a vulcanized rubber, wherein the vulcanized rubber is obtained by mixing and vulcanizing the conductive and antistatic rubber composition described above.

[0031] According to the present invention, the volume resistivity of the vulcanized rubber is 10 2 Ω·m to 10 9 Ω·m.

[0032] The third aspect of the present invention provides a method for preparing the aforementioned vulcanized rubber, wherein the method comprises:

[0033] (1) dispersing the carbon-based material into water to form a suspension containing the carbon-based material;

[0034] (2) using a saturated NaCl aqueous solution as a flocculant, mixing the base rubber with the suspension for co-coagulation, and filtering, washing and drying the obtained co-coagulated solid to obtain a base rubber / carbon-based material masterbatch;

[0035] (3) Mixing and vulcanizing the base rubber / carbon-based material masterbatch, the vulcanizing agent, the vulcanization accelerator, the vulcanization activator and the antioxidant to obtain a vulcanized rubber.

[0036] According to the present invention, in step (1), the process of dispersing the carbon-based material into water to form a suspension containing the carbon-based material is preferably carried out under ultrasonic conditions, wherein the ultrasonic frequency is 20000-200000 Hz.

[0037] According to the present invention, in step (2), the mixing conditions include: a stirring rate of 20-100 rpm, a temperature of 30-90°C, and a time of 5-600 min; preferably, a stirring rate of 40-90 rpm, a temperature of 40-80°C, and a time of 30-600 min.

[0038] According to the present invention, the co-coagulation conditions include: temperature of 40-90°C, time of 1-20 min; preferably, temperature of 40-80°C, time of 2-20 min.

[0039] According to the present invention, a highly dispersed carbon-based filler is compounded with a base rubber (styrene-butadiene rubber) latex, efficiently dispersed in the base rubber, and reduced in situ to a highly conductive filler during the compounding process, and a base rubber / carbon-based material masterbatch is obtained through flocculation and drying; then, the base rubber / carbon-based material masterbatch is mixed with a vulcanizing agent, a vulcanization accelerator, a vulcanization activator, and an antioxidant to obtain a rubber compound, and then the rubber compound is vulcanized.

[0040] According to the present invention, the mixing process includes two methods: open mixing and internal mixing.

[0041] According to the present invention, the open milling method refers to mixing all the components of the rubber composition in an open mill at 20-60° C. for 5-30 min.

[0042] According to the present invention, the banburying method refers to the first stage banburying of the components in the rubber composition except the vulcanizing agent, and then the second stage banburying of the vulcanizing agent. The first stage banburying refers to first adding the base rubber and the high thermal conductive filler, the mixing temperature is 145-150°C, the time is 3-5min, and then adding the remaining additives such as the vulcanizing activator, the mixing temperature is not higher than 150°C, and the mixing time is 1-3min.

[0043] According to the present invention, the method for preparing the vulcanized rubber is to vulcanize the mixed rubber at a pressure of 3-4 MPa and a temperature of 140-210° C. for 5-50 minutes to obtain the vulcanized rubber.

[0044] A fourth aspect of the present invention provides a use of the aforementioned vulcanized rubber in the preparation of a flexible resistance sensor.

[0045] A fifth aspect of the present invention provides a use of the aforementioned vulcanized rubber in the preparation of an antistatic rubber material.

[0046] In the present invention, the volume resistivity of the vulcanized rubber can meet the requirements of the conductive rubber material (10 2 Ω·m to 10 6 Ω·m) requirements; adjust the volume resistivity to 10 6 Ω·m to 10 9 Ω·m, and can also be used as antistatic rubber material.

[0047] The present invention will be described in detail below through examples.

[0048] In the following examples and comparative examples:

[0049] Experimental materials:

[0050] Styrene butadiene latex: solid content is 21%, produced by Chengdu Chuangwei New Materials Co., Ltd.

[0051] Graphene oxide: produced by Xiamen Kaina Graphene Technology Co., Ltd.

[0052] Carbon black: N330 carbon black, produced by Tianjin Black Cat Carbon Black Company.

[0053] Hydrazine hydrate, antioxidant 4010, accelerator CZ, zinc oxide, stearic acid, sulfur: purchased from Beijing Inokai Chemical Reagent Company, chemically pure.

[0054] Internal mixer (model BR1600 BANBURY, manufactured by Farrell Corporation, USA, mixing chamber volume 1.5L);

[0055] Resistivity of vulcanized rubber

[0056] The resistivity of the vulcanized rubber was tested on a four-probe resistivity meter (model RTS-8, produced by Anhemeng Technology Development Co., Ltd.).

[0057] The volume resistivity parameters were measured by voltammetry.

[0058] Examples 1-7

[0059] (1) dispersing graphene oxide in water by ultrasound at an ultrasonic frequency of 30000 Hz to form a suspension containing graphene oxide;

[0060] (2) A 20 wt% solidified styrene butadiene latex was mechanically stirred at a stirring rate of 100 rpm and mixed with graphene oxide suspensions having different contents (1, 3, 4, 5, 0.8, 6.2, and 6.5 phr, phr being relative to 100 parts by weight of the base rubber styrene butadiene rubber) respectively. After stirring for 30 minutes, hydrazine hydrate was added. The ratio of hydrazine hydrate to graphene oxide was 30 mL hydrazine hydrate per g of graphene oxide. The mixture was stirred at 100° C. for 30 minutes. The mixture was reduced for 24 hours, and then a saturated NaCl aqueous solution was added to the mixture for co-coagulation; the co-coagulated solid was filtered, washed with deionized water, and then dried in a vacuum oven at 60°C for 48 hours to obtain styrene-butadiene rubber / graphene oxide masterbatches with different graphene oxide contents. The masterbatches with graphene oxide contents of 1, 3, 4, 5, 0.8, 6.2, and 6.5 phr were coded G1, G3, G4, G5, G0.8, G6.2, and G6.5, respectively.

[0061] (3) Next, the styrene-butadiene rubber / graphene oxide masterbatch was mixed in an internal mixer according to the rubber composition formula and the mixing steps of the internal mixer, wherein Table 1 is the rubber combination formula and Table 2 is the mixing steps of the internal mixer, to obtain rubber mixes H1, H3, H4, H5, H0.8, H6.2, and H6.5.

[0062] H1, H3, H4, H5, H0.8, H6.2, and H6.5 were vulcanized on a flat vulcanizer at a pressure of 3.5 MPa and a temperature of 150°C for 30 min to obtain 2 mm thick sheet vulcanized rubbers S1, S3, S4, S5, S0.8, S6.2, and S6.5.

[0063] Example 8

[0064] Vulcanized rubber is prepared in the same manner as in Example 1, except that "graphene oxide" is replaced by "graphene"; and in step (2), there is no need to use hydrazine hydrate for reduction treatment.

[0065] Among them, the masterbatch code is GG1.

[0066] Rubber compound HH1.

[0067] As a result, a vulcanized rubber SS1 having a thickness of 2 mm was obtained.

[0068] The results are shown in Tables 1 and 2.

[0069] Comparative Examples 1-3

[0070] Vulcanized rubber was prepared in the same manner as in Examples 1-7, except that the content of graphene oxide was 0 parts by weight (Comparative Example 1), 9 parts by weight (Comparative Example 2), and 7 parts by weight (Comparative Example 3).

[0071] Among them, the masterbatch codes are G0, G9, and G7 respectively.

[0072] Rubber compounds H0, H9, H7.

[0073] As a result, 2 mm thick sheet-shaped vulcanized rubbers S0, S9 and S7 were obtained.

[0074] The results are shown in Tables 1 and 2.

[0075] Table 1

[0076]

[0077]

[0078] Note: phr represents the weight of each component per 100 parts by weight of base rubber. For example, 50 phr means that 50 grams of this substance should be added when the base rubber is 100 grams.

[0079] Table 2

[0080]

[0081]

[0082] *Note: The mixing was performed using a 1.5L internal mixer produced by Farrar. The feed amount was calculated as 7 times the formula, in g.

[0083] Test Case

[0084] The properties of the vulcanized rubbers prepared in Examples 1-8 and Comparative Examples 1-3 were tested, and the results are shown in Table 3, volume resistivity of the vulcanized rubbers.

[0085] Table 3

[0086]

[0087] in addition, Figure 1 Schematic diagram of the relationship between the volume resistivity and the content of graphene oxide of the vulcanized rubber prepared in Examples 1-4 and the vulcanized rubber prepared in Comparative Examples 1-3; From Tables 3 and Figure 1 It can be seen that the volume resistivity of the vulcanized rubber prepared by the graphene oxide / SBR composition shows a trend of first greatly decreasing and then slightly increasing with the increase of the graphene oxide content. The graphene oxide content corresponding to the lowest volume resistivity is 7phr. Compared with pure SBR, the volume resistivity of the vulcanized rubber with a graphene oxide content of 7phr is reduced by 12-13 orders of magnitude. When the graphene oxide content is 1phr, the volume resistivity of the vulcanized rubber composite material has reached the antistatic standard (10 6Ω·m~10 9 Ω·m), when the content of graphene oxide is above 3phr, the vulcanized rubber composite material can be used as a conductive rubber composite material (10 2 Ω·m~10 6 Ω·m). The rapid decrease in volume resistivity is because graphene oxide is in situ reduced to graphene by a reducing agent (hydrazine hydrate). When the graphene content is greater than the percolation threshold, the graphene oxide sheets contact each other to form a conductive network, that is, when the graphene oxide content is low (less than the percolation threshold content), the graphene oxide sheets are isolated and do not contact each other, making it difficult to conduct electricity effectively; when the content is high (greater than the percolation threshold content), there are enough graphene oxide sheets in the rubber material, and the sheets have the opportunity to contact each other to form a connected network, and the resistivity of the material will be significantly reduced.

[0088] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A conductive and antistatic rubber composition, characterized in that: The rubber composition comprises a base rubber, a carbon-based filler, a vulcanizer, a vulcanization accelerator, a vulcanization activator and an antioxidant, wherein the base rubber is styrene-butadiene rubber; the carbon-based filler is graphene and / or graphene oxide; and the content of the carbon-based filler is 0.8-6.5 parts by weight relative to 100 parts by weight of the base rubber.

2. The rubber composition according to claim 1, wherein The carbon-based filler is contained in an amount of 1 to 6.2 parts by weight, preferably 1 to 5 parts by weight, relative to 100 parts by weight of the base rubber.

3. The rubber composition according to claim 1 or 2, wherein: The base rubber is in the form of a base rubber latex; And / or, the solid content of the base rubber latex is 10-30wt%; And / or, the number of layers of the carbon-based filler is 1-16 layers.

4. The rubber composition according to claim 1, wherein Relative to 100 parts by weight of styrene-butadiene rubber, the content of the vulcanizing agent is 1-3 parts by weight, the content of the vulcanization activator is 3-6 parts by weight, the content of the vulcanization accelerator is 0.5-2 parts by weight, and the content of the antioxidant is 0.5-2 parts by weight; Preferably, relative to 100 parts by weight of styrene-butadiene rubber, the content of the vulcanizing agent is 1.25-2 parts by weight, the content of the vulcanization activator is 3.5-6 parts by weight, the content of the vulcanization accelerator is 1-2 parts by weight, and the content of the antioxidant is 1-2 parts by weight.

5. The rubber composition according to claim 1 or 4, wherein The vulcanizing agent is a sulfur donor, preferably, the vulcanizing agent is selected from one or more of ordinary sulfur S, oil-extended insoluble sulfur IS and sulfur-based vulcanizing agents; And / or, the vulcanization activator is an inorganic activator and / or an organic activator; and / or, the vulcanization accelerator is selected from one or more of sulfenamide accelerators, thiazole accelerators, thiuram accelerators and guanidine accelerators; And / or, the antioxidant is selected from one or more of amine antioxidants, quinoline antioxidants and benzimidazole antioxidants.

6. A vulcanized rubber, characterized in that: The vulcanized rubber is obtained by mixing and vulcanizing the conductive and antistatic rubber composition according to any one of claims 1 to 4.

7. The vulcanized rubber according to claim 6, wherein The volume resistivity of the vulcanized rubber is 10 2 Ω·m to 10 9 Ω·m.

8. A method for preparing the vulcanized rubber according to claim 6 or 7, characterized in that: The method includes: (1) dispersing the carbon-based material into water to form a suspension containing the carbon-based material; (2) using a saturated NaCl aqueous solution as a flocculant, mixing the base rubber with the suspension for co-coagulation, and filtering, washing and drying the obtained co-coagulated solid to obtain a base rubber / carbon-based material masterbatch; (3) Mixing and vulcanizing the base rubber / carbon-based material masterbatch, the vulcanizing agent, the vulcanization accelerator, the vulcanization activator and the antioxidant to obtain a vulcanized rubber.

9. The method according to claim 8, wherein: The mixing conditions include: stirring rate of 20-100 rpm, temperature of 30-90° C., and time of 5-600 min; And / or, the co-condensation conditions include: temperature of 40-90° C. and time of 1-20 min.

10. Use of the vulcanized rubber according to claim 6 or 7 in preparing a flexible resistance sensor.

11. Use of the vulcanized rubber according to claim 6 or 7 in preparing an antistatic rubber material.

Citation Information

Patent Citations

  • Rubber composition, vulcanized rubber and preparation method thereof

    CN106608989A

  • Carbon material enhanced rubber and preparing method thereof

    CN107955224A

  • Rubber composition, and vulcanized rubber, preparation method and applications thereof

    CN109836634A

  • Preparation method of high-dispersibility graphene oxide based rubber composite material

    CN109942913A

  • Graphene-reinforced antistatic rubber composition and preparation method thereof

    CN110698737A